Corrigendum to Featherstone (2006) "Yet more Evidence for a North-South Slope in the Australian Height Datum" - Featherstone, Will (Spatial Sciences Institute, Australia, 2007)
Since the publication of Featherstone (2006), it has been discovered that 339 astrogeodetic vertical deflection stations in Western Australia were omitted from the analysed data set. This was because many Western Australian observations had not been fully incorporated in the astrogeodetic database supplied by Geoscience Australia a few years ago. This corrigendum includes these data into the analysis in Featherstone (2006). While the conclusion that a north-south slope in the AHD remains valid, the inclusion of this additional data makes the evidence for this conclusion less compelling.